THE EFFECTS OF MACROECONOMIC VARIABLES ON PROFIT-SHARING YIELD PRICING - Mohammad Nur Rianto Al Arif (Economic Journal of Emerging Markets, 2011)
This research analyzes the infuence of macroeconomic variables such as Bank Indonesia rate, exchange rates, and inflation rate on pricing the profit-sharing yield for fundraising product in Indonesian Islamic banking. It uses a multiple regression to analyze the influence, and it also uses financial ratio and the profit-sharing yield from the previous period as control variables for this research. The analysis result shows that macroeconomic variables have significance influences on the pricing for profit-sharing yield in Islamic banking. Keyword: BI rate, exchange rate, profit-sharing yield, inflation rate, interest rateJEL classification: E40, G21, Z12